2012
DOI: 10.1111/j.1471-4159.2012.07658.x
|View full text |Cite
|
Sign up to set email alerts
|

Activated leukocyte cell adhesion molecule modulates neurotrophin signaling

Abstract: Development of the nervous system requires differentiating neurons to grow axons over great distances following long-and short-range signals that are controlled by distinct guidance systems. In general, long-distance acting molecules, such as growth factors, are soluble and bind receptors on the neuronal surface. In contrast, short-range membrane-associated molecules interact with surrounding cells and extracellular matrix, allowing for growth through diverse and changing environments. However, the boundaries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…NTR , and NCAM undergo trafficking in pH-neutral endosomes (22,30,46), and we hypothesize that this neutral environment prevents viral fusion and escape. To verify that the endosomal transport compartment used by RV-G pseudotyped HIV-1 vectors is also pH-neutral, motor neurons were incubated with the acidotropic probe LysoTracker DND for 2 h to label the acidic compartments before addition of RV-G pseudotyped HIV-1 DiO-labeled vectors for 2 h. Under these conditions, only 12% of all particles were positive for LysoTracker, and even when restricted to vectors that colocalize with p75 NTR (endosomal), only 20.74% of particles can be found in acidic compartments (Fig.…”
Section: Compartmentalized Motor Neuron Cultures Reveal Extensive Retmentioning
confidence: 94%
See 2 more Smart Citations
“…NTR , and NCAM undergo trafficking in pH-neutral endosomes (22,30,46), and we hypothesize that this neutral environment prevents viral fusion and escape. To verify that the endosomal transport compartment used by RV-G pseudotyped HIV-1 vectors is also pH-neutral, motor neurons were incubated with the acidotropic probe LysoTracker DND for 2 h to label the acidic compartments before addition of RV-G pseudotyped HIV-1 DiO-labeled vectors for 2 h. Under these conditions, only 12% of all particles were positive for LysoTracker, and even when restricted to vectors that colocalize with p75 NTR (endosomal), only 20.74% of particles can be found in acidic compartments (Fig.…”
Section: Compartmentalized Motor Neuron Cultures Reveal Extensive Retmentioning
confidence: 94%
“…6, D and E). It has recently been shown that NCAM undergoes retrograde transport in the same endosomal carriers as p75 NTR (30); however, it is not known whether the nAChR also undergoes retrograde trafficking. Using MFC cultures, retrograde transport of the labeled antagonist ␣-bungarotoxin was clearly observed (supplemental Fig.…”
Section: Compartmentalized Motor Neuron Cultures Reveal Extensive Retmentioning
confidence: 99%
See 1 more Smart Citation
“…Impairments in this process are associated with Alzheimer's disease, Huntington's disease, amyotrophic lateral sclerosis (ALS), and Charcot-Marie Tooth disease [151,158]. To investigate the composition of axonal retrogradely transported signaling endosomes, our laboratory developed a method using H C T coupled to magnetic iron oxide nanobeads (MIONs) for their purification and quantitative analysis by mass spectrometry [126,164].…”
Section: Axonal Retrograde Transport Of Cntmentioning
confidence: 99%
“…Finally, several CAMs, including activated leukocyte cell adhesion molecule (ALCAM), are transported in signaling endosomes together with neurotrophins like NGF. ALCAM potentiates neurotrophin signaling raising the possibility that ALCAM functions not only as an adhesion molecule but also in modulating the action of NGF (Wade et al, 2012), suggesting a close bidirectional regulation between neurotrophin and adhesion signaling. In summary, signaling from signaling endosomes not only allows for the spatial restriction of plasma membrane initiated signaling but also enables the assembly of distinct signaling complexes regulating actin dynamics through effector localization and adhesion formation/breakdown and signaling.…”
Section: Adhesion Formation Signaling and Turnovermentioning
confidence: 99%